Visceral obesity, but not metabolic syndrome, is associated with the presence of post-thrombotic syndrome. Issue 2 (August 2015) - Rattazzi, M.; Callegari, E.; Sponchiado, A.; Galliazzo, S.; Pagliara, V.; Villalta, S.; Pauletto, P.
Abstract Introduction The relationship between metabolic syndrome (MetS), and the development of post-thrombotic syndrome (PTS) is currently unknown. Materials and Methods We enrolled 120 patients with a previous episode of deep venous thrombosis (DVT) diagnosed more than 2 years apart from the enrollment. Presence of MetS was identified according to NCEP ATP III criteria and Villalta Score (VS) was used to establish the presence of PTS (VS ≥ 5). Results We identified 49 (40.8%) subjects with clinical diagnosed of PTS. Patients with or without PTS showed comparable age and temporal distance from DVT event. We observed higher BMI (p = 0.005) and waist circumference (p = 0.006) among subjects with VS ≥ 5 as compared to patients without PTS. No differences between the two groups were found in terms of lipid profile, blood pressure, diabetes, hs-CRP level and ongoing medications. The prevalence of MetS was equally distributed among patients with or without PTS (20% vs 26% respectively, p = 0.64). Among the individual components of MetS only the prevalence of visceral adiposity was significantly increased in subjects affected by PTS (OR 2.81, p = 0.008). Moreover, a significant linear correlation was found between VS and waist circumference in the entire cohort (r = 0, 354, p < 0.0001). Conclusion There is no evidence of association between MetS and PTS. However, the degree of visceral adiposity is strongly correlated with the presence and severity of post-thrombotic disease.